Community Assistance on the Responsibilities of Oil and Gas Mining Business License Holders for the Bati Tribe Community - Haliwela, Nancy Silvana; Lakburlawal, Mahrita Aprilya (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: Lack of understanding of the community's rights around the mining area and lack of understanding of the permit and approval procedures from the indigenous peoples before the operation of the oil and gas mining company. This is the basis for the consideration of the Civil Law section of the Faculty of Law, Pattimura University to carry out community service activities as a form of implementing the Tri Dharma of higher education.Purposes of The Devotion: Providing legal knowledge related to the procedures for mining business license holders who carry out their business activities in the mining area. Method of The Devotion: The method used is the legal counseling method in the Bati Tribe, Kian Darat District, Eastern Seram Regency.Results Main Findings of the Devotion: Activities of PT. Balam Energy Limited and PT. Bureau Geophysical Processing without going through a process of requesting approval from the Bati Tribe community, which has an area that will be used for oil and gas mining management activities. This is contrary to Article 33 paragraph (3) of Law Number 22 of 2001 concerning Oil and Gas (Oil and Gas Law). And it has implications for the use of land owned by indigenous peoples related to land that is considered to have sacred value, settlements, public facilities and infrastructure, nature reserves, cultural heritage and land belonging to customary law communities.